The effect of digital-based wound care education on the knowledge level of patients after percutaneous coronary intervention (pci) - Dewi, Mila Cahyasari; Wahyuningsih, Indah Sri; Suyanto, Suyanto (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Percutaneous Coronary Intervention (PCI) procedures may cause both physical and psychological effects, one of which is anxiety, often influenced by patients’ lack of knowledge regarding post-procedural wound care. Conventional education is considered suboptimal; therefore, innovation in digital-based educational approaches is needed. Purpose: To analyze the effect of digital-based wound care education on the level of knowledge among patients after Percutaneous Coronary Intervention (PCI). Method: A quasi-experimental pre-test–post-test nonequivalent control group design. A total of 44 respondents were recruited and divided into an intervention group and a control group. The intervention group received digital-based wound care education using video media, while the control group received education according to the hospital’s standard procedure. Knowledge level was measured using a knowledge questionnaire. Data were analyzed using the Wilcoxon test and Mann–Whitney test. Results: There was a significant increase in knowledge scores in both the intervention group and the control group after receiving post-PCI wound care education (p < 0.05). Between-group comparison analysis showed that post-intervention knowledge scores were significantly higher in the group that received digital-based education using animated video compared to the group that received the hospital’s standard education (p < 0.001). Conclusion: Digital-based education using animated video is more effective than the hospital’s standard education in improving knowledge among post-PCI patients. Keywords: Digital Education; Knowledge; PCI; Wound Care.